2003
DOI: 10.1016/s0167-9317(03)00121-7
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and application of a full wafer size micro/nanostencil for multiple length-scale surface patterning

Abstract: A tool and method for flexible and rapid surface patterning technique beyond lithography based on high-resolution shadow mask method, or nanostencil, is presented. This new type of miniaturized shadow mask is fabricated by a combination of MEMS processes and focused ion beam (FIB) milling. Thereby apertures in a 100-500 nm thick low-stress silicon nitride membrane in the size range from , 100 nm to . 100 mm were made. The stencil device is mechanically fixed on the surface and used as miniature shadow mask dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 11 publications
0
60
0
Order By: Relevance
“…1). The applications of nSL have been discussed elsewhere [3]. Full-wafer (100mm) nanostencil fabrication is based on advanced bulk and surface micromachining [4].…”
Section: A Full-wafer Nanostencilmentioning
confidence: 99%
“…1). The applications of nSL have been discussed elsewhere [3]. Full-wafer (100mm) nanostencil fabrication is based on advanced bulk and surface micromachining [4].…”
Section: A Full-wafer Nanostencilmentioning
confidence: 99%
“…Previous work [3] has demonstrated that a two dimensional array of Si nps embedded into a thin SiO 2 layer (from 5 to 10 nm) can be synthesized by ultra-low energy ion implantation (ULE-II) (1 keV) followed by thermal annealing (under N 2 or a slight mixture of N 2 + 1.5% O 2 at 900 to 1000 °C). At the same time, stencil mask process has been developed to transfer patterns into a selective area of a substrate either by metal deposition [4], ion beam lithography [5] or masked ion implantation [6]. Thus, the combination of ULE-II and stencil mask can be as an alternative method to locally synthesize a controlled number of self-organized nps.…”
Section: Introductionmentioning
confidence: 99%
“…These new methods include: indentation of polymers by nanoimprint lithography (NIL) [1,2], local deposition of molecules via a stamp by microcontact printing (CP) or soft-lithography [3,4], or via dip-pen nanolithography (DPN) [5], nanoscale fluidic dispensing (NADIS) [6] and localized material deposition through ultra-miniature shadow masks (nanostencils) [7][8][9][10]. The stencil method has the advantage of being a direct vacuum patterning technology, i.e.…”
Section: Introductionmentioning
confidence: 99%